2014
DOI: 10.7603/s40681-014-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Personalized Therapy for Castration-Resistant Prostate Cancer

Abstract: With advances in molecular biologic and genomic technology, detailed molecular mechanisms for development of castration-resistant prostate cancer (CRPC) have surfaced. Metastatic prostate cancer (PCa) no longer represents an end stage, with many emerging therapeutic agents approved as effective in prolonging survival of patients from either pre- or post-docetaxel stage. Given tumor heterogeneity in patients, a one-size-fits-all theory for curative therapy remains questionable. With the support of evidence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 71 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…For patients with elevated risk factors or cancer recurrence, radiation therapy (RT) is one of the effective treatment options ( Dearnaley et al, 1999 ; Liu et al, 2014c ). However, a significant proportion of patients develop metastatic disease where RT is ineffective due to the development of radioresistance in PCa cells ( Hummerich et al, 2006 ; Liu et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…For patients with elevated risk factors or cancer recurrence, radiation therapy (RT) is one of the effective treatment options ( Dearnaley et al, 1999 ; Liu et al, 2014c ). However, a significant proportion of patients develop metastatic disease where RT is ineffective due to the development of radioresistance in PCa cells ( Hummerich et al, 2006 ; Liu et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…For patients with inoperable disease or high risk of cancer recurrence, radiation therapy is considered an optimal choice [2, 3]. However, some of these patients present with intrinsic radio-resistance or develop radio-resistance prior to or after radiotherapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…The main biologically active form of endogenous androgens is testosterone through the action of a P450 family member (commonly known as 5α-reductase). Androgen is an important factor in body composition at age-associated changes in men —for instance, in an increase in fat mass and a decrease in lean body mass [ 61 ]. Epidemiological studies have shown a bidirectional relationship between low testosterone levels and obesity in men [ 62 ].…”
Section: Candidate Genes/pathwaysmentioning
confidence: 99%